Protective effect of Spirulina in the ovary of rats against Doxorubicin toxicity - Öztürk, Şamil; İrkin, Latife Ceyda (Revista Científica de la Facultad de Ciencias Veterinarias, 2024)
Doxorubicin (Dox) is an anti–cancer agent used of ovarian, breast, liver, lung cancers and solid tumors such as leukemia and lymphoma treatment. However, since it is an antineoplastic agent with a high toxic effect, it causes toxicity on many organs and tissues in the organism. Spirulina spp. (SP) contains phytopigments such as β–carotene, tocopherols and xanthophylls and is a natural source of vitamin A as well as its anticarcinogenic effect. For these reasons, this study was planned to experimentally reveal the antioxidant and protective effects of SP on Dox–induced reproductive toxicity in female rats. In the study, histopathological evaluation was performed after Hematoxylin–Eosin staining in female rats with Dox toxicity. The distribution of GSK–3β for cell proliferation, HIF–1α for oxidative stress and VEGF for vascularization were evaluated. TUNEL staining was performed to determine apoptosis. It was determined that SP prevented tissue damage on the ovarian tissue of rats with Dox toxicity, and this positive effect was achieved through factors such as oxidative stress (HIF–1α), vascularization (VEGF) and inhibition of cell death (Apoptosis). It has been observed that SP treatment to be applied after chemotherapy is effective in protecting both the developing follicles and the primordial follicle pool.